Isolation and Molecular Characterization of Potential Plant Growth Promoting Bacillus cereus GGBSTD1 and Pseudomonas spp. GGBSTD3 from Vermisources - Balayogan Sivasankari; Marimuthu Anandharaj (Advances in Agriculture)
Vermicompost was prepared from leaf materials of Gliricidia sepium + Cassia auriculata + Leucaena leucocephala with cow dung (1 : 1 : 2) using Eudrilus eugeniae (Kinberg) and Eisenia fetida for 60 days. Nineteen bacterial strains which have the capability to fix nitrogen, solubilize inorganic phosphate, and produce phytohormones were isolated from vermicompost, vermisources, and earthworm (fore, mid, and hind) guts and tested for plant growth studies. Among the bacterial strains only five strains had both activities; among the five Bacillus spp. showed more nitrogen fixing activity and Pseudomonas spp. showed more phosphate solubilizing activity. Hence these bacterial strains were selected for further molecular analysis and identified Bacillus cereus GGBSTD1 and Pseudomonas spp. GGBSTD3. Plant growth studies use these two organisms separately and as consortium (Bacillus cereus + Pseudomonas spp.) in (1 : 1) ratio at different concentrations using Vigna unguiculata (L.) Walp. at different day intervals. The germination percent, shoot length, root length, leaf area, chlorophyll a content of the leaves, chlorophyll b content of the leaves, total chlorophyll content of the leaves, fresh weight of the whole plant, and dry weight of the whole plant were significantly enhanced by the consortium (Bacillus cereus + Pseudomonas spp.) of two organisms at 5 mL concentrations on the 15th day compared to others.